Prevalence of bronchial asthma in school going children: A cross-sectional study from Uttar Pradesh - Tazeen Shamshad; Najam Khalique; Mohammad Shameem; Mohammad Salman Shah; Tabassum Nawab (Wolters Kluwer Medknow Publications, 2022)
Background: Asthma is coined as a chronic inflammatory disorder and disarrays of the airways and respiratory tract which manifests as recurrent episodes of wheezing, breathlessness, chest tightness, and cough. The World Health Organization recognizes asthma as a major health problem. Although asthma can occur at any age, children and young adults are the age groups which are affected more commonly. Objectives: The objective of this study is to find the prevalence of bronchial asthma in school-going children (6-16 years) and its associated factors. Materials and Methods: A cross-sectional study among the school-going children in the age group of 6-16 years was done in the field practice areas of urban health and training center and rural health and training center of the Department of Community Medicine, JNMCH, A. M. U., Aligarh, U.P. the study done for a period of one year. The validated questionnaire (International Study on Allergy and Asthma in Childhood) was used. The sample size was taken as 902. The data were entered and analyzed in the SPSS statistical software version 20.0. Chi-square was used. Results: The prevalence of asthma among the study population was found to be 26.9%. Family history of smoking and history of allergy in an individual came out to be a significant factor associated with asthma. The association is also significant between asthma and the diet of an individual. Conclusions: Asthma among school children is a public health problem in urban and rural areas. There was a rising pattern in the prevalence of asthma at national and subnational levels.